Effects of Proton Pump Inhibitor Therapy, H. pylori Infection and Gastric Preneoplastic Pathology on Fasting Serum Gastrin Concentrations - Veysey-Smith, Reuben; Moore, Andrew R.; Murugesan, Senthil V.; Tiszlavicz, Laszlo; Dockray, Graham J.; Varro, Andrea; Pritchard, D. Mark (Frontiers in Endocrinology, 2021)
Background: Hypergastrinaemia occasionally indicates the presence of a gastrinoma. However it is much more commonly associated with various benign causes including proton pump inhibitor (PPI) use, Helicobacter pylori infection and/or atrophic gastritis. The extent to which these factors interact to influence fasting serum gastrin concentrations remains incompletely understood. Materials and Methods: Fasting serum gastrin concentrations were measured by radioimmunoassay in 1,400 patients attending for diagnostic oesophagogastroduodenoscopy. After exclusions, 982 patients were divided into four groups and their results analysed. We compared gastrin concentrations in normal patients (no H. pylori infection, no PPI use and no histological evidence of gastric preneoplasia (n=233)), with those in patients who were taking regular PPIs (H. pylori negative with no gastric preneoplasia (n=301)), patients who had active H. pylori infection but no gastric preneoplasia (n=164) and patients with histologically confirmed gastric preneoplasia (n=284). Results: Median fasting gastrin concentration in the normal group was 20pM and was significantly increased in PPI users (46pM, p<0.0001), patients with active H. pylori infection (27pM, p<0.0001), and patients with antral (25pM, p<0.01) or corpus (48pM, p<0.0001) gastric preneoplasia. PPI use resulted in further significant increases in fasting serum gastrin concentrations in patients who were infected with H. pylori (50pM, n=56) or who had antral gastric preneoplasia (53pM, n=87), but did not significantly alter serum gastrin concentrations in patients with corpus preneoplasia (90pM, n=66). Conclusions: PPI use, H. pylori infection and atrophic gastritis all caused significant elevations of median fasting gastrin concentrations. However, several patients who had potential risk factors for hypergastrinaemia still demonstrated fasting serum gastrin concentrations within the normal range.